2017
DOI: 10.1021/acs.langmuir.7b02290
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubble Water’s Promotion Effect of Barley (Hordeum vulgare L.) Sprouts Supported by RNA-Seq Analysis

Abstract: The physiological promotion effect of nanobubble (NB) water on living organisms is still a poorly understood phenomenon which was discovered 1 decade ago. Here, we analyzed the barley (Hordeum vulgare L.) embryo transcriptome following the exposure to NB water and low-concentration hydrogen peroxide (HO) using RNA-Seq. We found that 349 genes were differentially expressed after 24 h exposure to NB water and 97 genes were differentially expressed after exposure to HO solution. Gene ontology enrichment and clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…Based on Figure 2.C., UFB priming treatment was significantly affected the growth rate of gmelina seeds, both on noninjection and injection UFB treatment. Similar to a study by Liu et al (2017), that the density of micro-nano bubbles affects the germination percentage at the end of the observation time and accelerates the germination of spinach and wheat seeds. The low density of micro-nano bubbles does not imply negative effects on the observed seeds but manages to increase its germination properties.…”
Section: Seed Viability and Vigor Based On Various Priming Treatmentssupporting
confidence: 74%
See 1 more Smart Citation
“…Based on Figure 2.C., UFB priming treatment was significantly affected the growth rate of gmelina seeds, both on noninjection and injection UFB treatment. Similar to a study by Liu et al (2017), that the density of micro-nano bubbles affects the germination percentage at the end of the observation time and accelerates the germination of spinach and wheat seeds. The low density of micro-nano bubbles does not imply negative effects on the observed seeds but manages to increase its germination properties.…”
Section: Seed Viability and Vigor Based On Various Priming Treatmentssupporting
confidence: 74%
“…According to Liu et al (2014), water containing micro-nano bubbles can form Reactive Oxygen Species (ROS) or free radicals. ROS or free radicals have a crucial role in the germination process (Liu et al 2017). Essentially, free radicals can increase the physiological activity of living things, especially plants, but in high figures might cause damage to the plant (Liu et al 2014).…”
Section: Seed Viability and Vigor Based On Various Priming Treatmentsmentioning
confidence: 99%
“…Similar data were acquired from investigating lettuce grow for hydroponic lettuce culture system and usage of microbubble-saturated water compared to macrobubble-saturated water (Park and Kurata, 2009). The reason of higher growth rate of plants was presented by Liu et al (2017) who performed RNAsequencing of barley seeds which had contact with nanodispersion of oxygen and showed that presence of nanobubbles induce the expression of genes responsible for cell divisions and elongation (Liu et al, 2017). Ahmed et al (2018) showed that the seeds of different plant species reacted differently to presence of nanobubbles and as such the effect on germination may be plant-specific (Ahmed et al, 2018a).…”
Section: Nanobubble Applications In Environmental Processesmentioning
confidence: 60%
“…The reason of higher growth rate of plants was presented by Liu et al . (2017) who performed RNA‐sequencing of barley seeds which had contact with nanodispersion of oxygen and showed that presence of nanobubbles induce the expression of genes responsible for cell divisions and elongation (Liu et al ., 2017). Ahmed et al .…”
Section: Nanobubble Applications In Environmental Processesmentioning
confidence: 99%
“…Furthermore, NBs have been found to promote growth of different species of plants and animals [ 18 ] by speeding up their metabolism. [ 19 ] These results have significant ramifications on productivity. Especially in aquaculture installations by providing more oxygen and at the same time promoting fish growth and reducing the required amounts of antibiotics.…”
Section: Introductionmentioning
confidence: 99%